PERBANDINGAN TEBAL PERKERASAN JALAN KAKU DENGAN METODE PD-T-14-2003 DAN MDPJ 2017 (Studi Kasus Jl.Yos Sudarso, Kota Dumai) - Nasution, Muhammad Azizi; Fajarriani, Nanda; Idham, Muhammad (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2019)
Road is an infrastructure that plays an important role in the flow of traffic, so that if there is damage to the road on a road, damage investigations need to be carried out. The damage investigation in this study used the Bina Marga method while the calculation of pavement thickness using Bina Marga 2003 and the 2017 Road Pavement Design Manual. The results of the pavement investigation on Jl. Yos Sudarso which had flexible pavement received a priority value of 3, namely handling of road improvement Planning rigid pavement thickness using Bina Marga 2003 on Jl. Yos Sudarso of 170 mm and the 2017 Pavement Design Manual is 180 mm thick. In addition, the calculation of the budget plan on Jl. Yos Sudarso based on the 2003 Bina Marga Method and the 2017 Road Pavement Design Manual are Rp. 5,684,150,000 and Rp. 5,383,700,000 with the use of Jl. Yos Sudarso as a type III C collector road.